Hong Kong high school students' perceptions of the new secondary school curriculum - Diya Dou; Daniel T. L. Shek (Frontiers Media S.A., 2022)
BackgroundThe New Senior Secondary (NSS) curriculum in Hong Kong aims to change the exam-oriented culture and promote students' all-around development. This reform emphasizes student-centered learning and promotes a shift from a top-down approach to school-based management, with the ultimate goal to help students become lifelong learners. This study examined students' perceptions of the NSS curriculum with a focus on their noncognitive development (e.g., self-understanding, positive values, purpose in life, and resilience).MethodsThe data were collected from 3,498 Secondary 6 students in Hong Kong (Girls: 47.7%; Mean age: 17.33 years) using a self-reported questionnaire in 2015. We examined the psychometric properties of the instrument, "Perceptions of the New Secondary School Curriculum" (PNSC), and conducted multigroup CFA to evaluate the measurement invariance of PNSC across genders. Paired t-test analysis was used to examine whether students perceived the junior and senior secondary curricula differently. A series of multivariate analysis of variance (MANOVA) were conducted to examine students' perceptions of the curriculum by gender and by academic performance level.ResultsResults based on percentage responses showed that most students liked the curriculum and acknowledged its benefits in promoting their noncognitive development. However, substantial proportions of the students also reported relatively negative responses to some items, particularly their fondness for senior secondary education. Students generally reported higher fondness for the junior secondary curriculum than for the senior secondary curriculum. Girls had more positive perceptions of the NSS curriculum than did boys. High-performing students liked the NSS curriculum the most and perceived the most benefits of the curriculum in promoting their noncognitive skills, whereas low-performing students showed the lowest levels of fondness for/interest in the curriculum and perceived benefits.ConclusionsOur findings support previous evidence showing initial success in promoting students' noncognitive skills but also alert educators and policymakers that the curriculum should not leave the low-performing students behind. Collective efforts from schools, educational bureaus, researchers, and policymakers are needed to take appropriate measures to cater to students' balanced development.